Kesesuaian Pemeriksaan jamur antara pewarnaan periodic acid schiff(PAS) dan KOH pada flour albus ibu hamil di RSUD dr Soetomo Surabaya - Shinta arya; Arthur pohan kawilarang (Universitas Nahdlatul Ulama Surabaya, 2020)
Background: Candidiasis vaginalis is a form of vaginal infection by Candida spp, estimated to occur in women of childbearing age in 70-75% of the cases. Clinical history, symptoms and laboratory examinations are very important to diagnose candidiasis vaginalis. Vaginal discharge examination can be done by direct or wet, and culture examination. Microscopic examination can be used to prove the existence of yeast form of Candida. This method is simple, can be applied in clinical microbiology laboratory with limited resources and is considered effective because it is cheap and results are obtained in a short time compared to culture. Detection of fungi by Periodic Acid Schiff (PAS) staining is visually better than KOH. The aim of this study is to analyze the concordance between Periodic Acid Schiff (PAS) staining and KOH method for fungal detection in flour albus from pregnant women. Method: This research is a descriptive observational study to figure out the suitability of Periodic Acid Schiff (PAS) staining and KOH method for fungal detection in flour albus from pregnant women with cross sectional approach. Samples were collected in the form of 30 vaginal discharge specimens taken from pregnant women and sent to the Clinical Microbiology Laboratory Dr. Soetomo Surabaya. The study was conducted in July - August 2019. Result: There was a significant difference in fungal detection between Periodic Acid Schiff (PAS) staining (56.7%, 17 samples) and 20% KOH method (6 samples) out of 30 samples (p=0.017). The concordance between Periodic Acid Schiff (PAS) staining and KOH method for fungal detection in flour albus from pregnant women is low (Kappa=0.321). Conclusion: Periodic Acid Schiff (PAS) staining detects more fungi when compared to KOH, and therefore is considered as a better method. Keywords: Flour albus, pregnancy, Periodic Acid Schiff (PAS), KOH.